USA CIA activity in the western part of USSR. Declissified archives and possibilities to research history of post war Lithuania - Jurkutė, Mingailė (Genocidas ir rezistencija, 2017)
Since the beginning of the guerrilla fights, since the Atlantic Charter, there has been a general belief that ‘America supports us’. Although the operations of the United States Central Intelligence Agency (CIA) were classified as ‘secret’, the facts of cooperation with the secret services of Europe and the United States were well-known in the relevant circles of the diaspora. Although the CIA operations were a well-known fact from the very beginning, there is almost no information in Lithuanian historiography about their nature, specifics and details. The reconstruction of the resistance organisations’ links or cooperation with the Western secret services has so far mainly relied on two groups of sources: the personal archives of diaspora figures and, to some extent, the documents of Soviet repressive structures. There is almost nothing about US military plans or preparations for war, although there are various considerations of ‘war hopes’, ‘high’ or ‘futile’, sometimes equivalent to the terminology of the ‘war myth’.
Keywords: Lithuania; USA; CIA; Soviet occupation; armed resistance